2022
DOI: 10.1080/07011784.2022.2032367
|View full text |Cite
|
Sign up to set email alerts
|

Baseline geographic information on wildfire-watershed risk in Canada: needs, gaps, and opportunities

Abstract: As the pressures on water supply from shifting forest disturbance regimes continue to escalate, researchers are being asked to answer increasingly complex questions. However, many questions in wildfire-watershed risk (WWR) research remained unaddressed due to a paucity of relevant datasets. There are, indeed, many fundamental processes we do not understand that require additional data collection to develop risk management frameworks.As such, WWR researchers and managers face a paradox in their need to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Water-quality monitoring in watersheds that are vulnerable to wildfire, including parameters listed in (Table 1), would provide critical baseline data for assessing how wildfires impact watersheds. Improved postwildfire water-modeling capacity, driven by data integration that reduces prediction uncertainty, would further advance the ability of the wildfire-science community to provide actionable intelligence for water supply planning and protection (e.g., Neris et al, 2021;Nyman et al, 2021;Steblein et al, 2021;Robinne et al, 2022). Remotely sensed characterization of post-wildfire water quality could provide a globally available sentinel of water-supply hazards.…”
Section: Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-quality monitoring in watersheds that are vulnerable to wildfire, including parameters listed in (Table 1), would provide critical baseline data for assessing how wildfires impact watersheds. Improved postwildfire water-modeling capacity, driven by data integration that reduces prediction uncertainty, would further advance the ability of the wildfire-science community to provide actionable intelligence for water supply planning and protection (e.g., Neris et al, 2021;Nyman et al, 2021;Steblein et al, 2021;Robinne et al, 2022). Remotely sensed characterization of post-wildfire water quality could provide a globally available sentinel of water-supply hazards.…”
Section: Opportunitiesmentioning
confidence: 99%
“…In addition, because wildfires can reduce the threshold precipitation intensity at which overland flow occurs, post-wildfire stream discharge and sediment concentrations can be orders of magnitude greater than they would have been for similar storms pre-wildfire (Wondzell and King, 2003;Murphy et al, 2015), which poses challenges to current monitoring capabilities. As a result of these challenges, there are numerous gaps in post-wildfire water-quality data (Yu and Cheng, 2008;Rust et al, 2018;Basso et al, 2022;Hampton et al, 2022;Paul et al, 2022;Robinne et al, 2022;Raoelison et al, 2023), as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%